Analisis Perhitungan Dalam Optimalisasi Manajemen Inventori Pada Pengadaan Bahan Baku dengan Metode Safety Stock di PT ABC - Nandana Athila Nafi; Mega Cattleya P.A. Islami (Jurnal Serambi Engineering, 2025)
This study aims to analyse the calculations involved in optimising inventory management for raw material procurement at PT ABC using the safety stock method. In an increasingly competitive industrial context, efficient inventory management is crucial to maintain operational continuity and minimise costs. The safety stock method is used to anticipate fluctuations in demand and delays in delivery, thereby reducing the risk of raw material shortages. This research uses historical sales data and procurement lead times to calculate the optimal safety stock level. The analysis results indicate that the implementation of the safety stock method can improve inventory management efficiency, reduce inventory carrying costs and ensure timely availability of raw materials. In addition, this study provides recommendations for PT ABC to continuously monitor and adjust safety stock levels in response to changes in demand and market conditions. Thus, this research is expected to contribute to the development of better inventory management strategies within the company.